5(x – 2) > 3(x + 2)
Question
Updated 4/3/2015 10:58:00 AM
This conversation has been flagged as incorrect.
Flagged by alfred123 [4/3/2015 10:58:00 AM]
f
Original conversation
User: 5(x – 2) > 3(x + 2)

Weegy: You would need to have the value ofeither y or x to calculate the other.
cimrie|Points 1499|

User: simplify 5(x – 2) > 3(x + 2)

Question
Updated 4/3/2015 10:58:00 AM
This conversation has been flagged as incorrect.
Flagged by alfred123 [4/3/2015 10:58:00 AM]
Rating
8
5(x – 2) > 3(x + 2)

5x - 10 > 3x + 6;

5x - 3x > 6 + 10;

2x > 16;

x > 16/2

x > 8
Confirmed by yumdrea [4/3/2015 7:09:12 PM]

Questions asked by the same visitor
3x – 1 – x = 3x + 5
Weegy: The expression 3x? represents 3(x)(x) User: solve for x (More)
Question
Updated 5/13/2014 4:15:54 AM
3x – 1 – x = 3x + 5;

2x - 1 = 3x + 5;

2x - 3x = 5 + 1;

-x = 6;

x = -6
5(x + 3)=7(x – 5)
Question
Updated 11/13/2011 8:17:41 PM
The answer to the equation: 5(x + 3)=7(x – 5) is to rewrite the equation as 5x + 15=7x – 35 and then adding like variables: 50=2x and then solving for x which is x=25.
Confirmed by andrewpallarca [7/1/2014 1:25:45 PM]
5(x+3)=7(x–5) solve for x User: Graph the equation Y = 4x – 3
Weegy: Sorry can't show the graph. But here are the values. x=1, y= 1/ x=2, y=5. User: Graph the equation 4x – 5 = 2x – y User: 4x – 5 = 2x – y Weegy: 5/2x+1/4x=7/4+x SOLUTION: 5/2x+1/4x-x=7/4 >> (5/2+1/4-1)x=7/4 >> (7/4)x=7/4 >> x=(7/4)/(7/4) >> x=1 User: graph 4x – 5 = 2x – y Weegy: Sorry but I cannot graph that equation since we don't have a tool to attach a file on our answers (More)
Question
Updated 3/14/2012 8:14:11 AM
5(x+3)=7(x–5) solve for x
5x+15 = 7x -35
5x-7x = -15-35
-2x = -50
x = 25
Confirmed by andrewpallarca [6/16/2014 12:28:23 PM]
solve 15x + 2 = 9x + 28
Weegy: 15x + 2 = 9x + 28, 15x - 9x = 28 - 2, 6x = 26, x = 26/6, x = 4 2/6, simplified: x = 4 1/3 (More)
Question
x + 6 User: 5x + 3
Weegy: 5x + 3 User: 6x – 5 > -17 (More)
Question
Updated 1/1/2018 10:04:05 PM
x + 6 < 2
x < 2 - 6
x < -4